2021
DOI: 10.21926/obm.icm.2201005
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor Therapy Using Vestibular Stimulation: A Complementary Method for ‘Treatment’ of Developmental Coordination Disorder and a Possible Way to Awaken the Innate Potential for a Physically Active Life

Abstract: The aim of this commentary is to present characteristics of an “unidentified psychological barrier,” which we previously have speculated to be associated with vestibular underachievement, an overlooked part for the understanding of the resistance to physical activity as well as in the assessments and interventions of developmental coordination disorder (DCD). Furthermore, we will discuss the importance of its identification and how to push knowledge forward. A delayed or partly absent sensorimotor development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Although the authors were hesitant regarding the involvement of a socio-cultural context, from my point of view, it is important to keep “a sense of coherence” (Antonovsky, 1996) in mind. “No man is an island entire of himself” (John Donne); we are all part of a context, a brain–body–world interaction (BBWI) (Clark, 1999; Niklasson et al , 2022).…”
Section: Art For Art’s Sakementioning
confidence: 99%
“…Although the authors were hesitant regarding the involvement of a socio-cultural context, from my point of view, it is important to keep “a sense of coherence” (Antonovsky, 1996) in mind. “No man is an island entire of himself” (John Donne); we are all part of a context, a brain–body–world interaction (BBWI) (Clark, 1999; Niklasson et al , 2022).…”
Section: Art For Art’s Sakementioning
confidence: 99%
“…The most important sources for neural activity are the nonadaptive sensory receptors of the vestibular system which respond to the force of gravity [7]. The vestibular nuclei are functional by the 11:th week prenatally and the vestibular system is mature by the 21st week [1]. Despite its early development the vestibular system is, according to Piontelli [7], the most overlooked sensory capacity of the fetus and there is still no consensus concerning its activity in utero.…”
Section: The Vestibular Systemmentioning
confidence: 99%
“…In a recent publication [1] we concluded that, "A delayed or partly absent sensorimotor development for an otherwise healthy infant might be a strong enough sign of an underachieving vestibular system. The significance of an aberrant Moro reflex beyond 6 months of age should not the least be an adequate reason for further enquiry."…”
Section: Introductionmentioning
confidence: 98%